Colonoscopy‐assisted percutaneous sigmoidopexy for a complete rectal prolapse: A case report. Issue 1 (17th October 2022) - Takahashi, Junji; Yoshida, Masashi; Kamada, Teppei; Nakaseko, Yuichi; Nakashima, Keigo; Suzuki, Norihiko; Ohdaira, Hironori; Suzuki, Yutaka
Abstract: Colonoscopy‐assisted percutaneous sigmoidopexy is a simple and swift procedure that does not require general anesthesia. While we first developed this procedure for treating sigmoid volvulus, we herein present the first case in which we used it to correct a complete rectal prolapse in an older patient. Existing treatment modalities for rectal prolapses are limited by high recurrence rates, greater invasiveness, and greater complications; thus, there is a need for minimally invasive techniques that are associated with lower recurrence rates and fewer complications. In this case, a woman in her 90s complained of persistent fecal incontinence, dysuria, anal pain, and difficulty in walking. She was diagnosed with a complete rectal prolapse of 15 cm and was treated with colonoscopy‐assisted percutaneous sigmoidopexy. The sigmoid colon was tractioned colonoscopically and fixed to the abdominal wall to immobilize the prolapsed rectum. The patient developed no complications intraoperatively and postoperatively and experienced no recurrence during a 5‐year postoperative period. This report documents the first case wherein colonoscopy‐assisted percutaneous sigmoidopexy was used successfully to correct a complete rectal prolapse.